BIOMECHANICAL COMPARISON OF TRANSPEDICULAR FIXATION METHODS UNDER ROTATIONAL LOADING FOR OPTIMIZING SURGERY ON THE THORACOLUMBAR JUNCTION OF THE SPINE - O.S. NEKHLOPOCHYN; V.V. VERBOV; I.V. CHESHUK; M.V. VORODI; M.YU. KARPINSKY; O.V. YARESKO (Avicenna Tajik State Medical University, 2024)
Objective: To analyze various transpedicular (TP) fixation options for the thoracolumbar junction (TLJ) under rotational loads. Methods: A finite element model of the thoracolumbar spine was generated as part of a study. The model includes vertebrae Th9-Th11 and L2-L5 but excludes Th12 and L1. The model also integrates metallic structural elements, such as a vertebral body replacement (VBR) implant (interbody cage) and a TP system. We modeled the result of decompressive-stabilizing surgery for type C vertebral injuries (according to the classification scheme proposed by F. Magerl et al, 1994). The study analyzes four variants of TP fixation with different screw lengths and the influence of the presence or absence of transverse reinforcements. Results: It was found that during rotational loading, the maximum stress in bone structures occurs at the contact surface between the VBRs and the endplates of both adjacent vertebrae to the removed ones. In metallic hardware, the highest stress is observed on the interbody cage and in the TP screws installed in the Th10 and Th11 vertebral bodies. A comparison of different stabilization options reveals that the TP system with short monocortical screws and without transverse reinforcements provides moderate levels of stress. The use of bicortical screws without crosslinks results in a significant increase in stress, especially at the contact surface in the vertebral endplates and the intervertebral support device. On the other hand, the use of transverse reinforcements with short screws reduces stress, providing an optimal stabilization option. However, bicortical screws with crosslinks did not show significant benefits. Conclusion: Upon scrutinizing the biomechanical efficiency of different TP fixation methods, it has been determined that utilizing a TP system equipped with monocortical screws and two crosslinks results in the most even stress distribution caused by the rotational load.